Аналіз державних інструментів стимулювання інноваційних технологій в умовах глобальної цифровізації - Мазур, Ю.О. (Економіка промисловості, 2020)
Використання інноваційних технологій передбачає розробку з боку підприємства науково-конструкторських стратегій оновлення процесу виробництва продукції, а з боку держави - ефективних інструментів стимулювання інноваційної активності суб’єктів господарювання. З урахуванням того, що податкове стимулювання призводить до недоотримання державою доходів або ресурсів, які могли б бути використані в інших формах державної підтримки, для оцінки ефективності їх використання доцільно проаналізувати величину витрат на їх надання та доходів. Розглянуто місце інновацій у господарській діяльності підприємств та їх вплив на економіку в умовах глобальної цифровізації. Визначено напрями впровадження інновацій та їх значущість у реальному секторі економіки.У багатьох країнах світу розробляються та вдосконалюються стратегічні програми розвитку інноваційної діяльності підприємств, аналіз яких засвідчив їх доцільність в умовах упровадження новітніх цифрових технологій. Позначено проблеми, які мають країни з валовим доходом нижче середнього, у тому числі Україна. З урахуванням особливостей державних інструментів щодо інноваційної активності підприємств обґрунтовано доцільність використання різних видів підтримки розвитку інноваційних технологій - не тільки державою, але і науково-дослідними установами та самими підприємствами. Проаналізовано ефективність податкових стимулів інноваційної активності підприємств у провідних країнах світу. Розглянуто сучасні аналітичні інструменти оцінки податкового стимулювання підприємств та визначено ефективність податкових стимулів щодо їх інноваційної активності в умовах глобальної цифровізації. Обґрунтовано можливі напрями використання державних інструментів стимулювання інноваційних технологій в Україні. Головна вимога податкового стимулювання національних інновацій полягає у здійсненні суб'єктом господарювання систематичної діяльності, спрямованої на досягнення науково-технічного прогресу в умовах наукової або технологічної невизначеності. Податкові стимули мають бути доступними інноваційним підприємствам незалежно від їх територіального розташування в межах держави та розміру; дозволяти віднімати із суми податку на прибуток інноваційних підприємств частину кваліфікованих витрат; надаватися на безповоротній основі протягом законодавчо встановленого періоду часу; розроблятися з урахуванням зведення до мінімуму можливостей розвитку корупції при наданні стимулів і зловживань платниками податків при їх використанні. Оцінка урядом очікуваних витрат і вигід від податково-бюджетного стимулювання інноваційної діяльності підприємств України має бути аналогічною оцінці інших видів податкових витрат з урахуванням інституційних особливостей розвитку національної економіки. Использование инновационных технологий предполагает разработку со стороны предприятия научно-конструкторских стратегий обновления процесса производства продукции, а со стороны государства - эффективных инструментов стимулирования инновационной активности субъектов хозяйствования. С учетом того, что налоговое стимулирование приводит к недополучению государством доходов или ресурсов, которые могли бы быть использованы в других формах государственной поддержки, для оценки эффективности их использования целесообразно проанализировать величину расходов на их предоставление и доходов. Рассмотрено место инноваций в хозяйственной деятельности предприятий и их влияние на экономику в условиях глобальной цифровизации. Определены направления внедрения инноваций и их значимость в реальном секторе экономики.Во многих странах мира разрабатываются и совершенствуются стратегические программы развития инновационной деятельности предприятий, анализ которых показал их уместность в условиях внедрения новейших цифровых технологий. Обозначены проблемы, с которыми сталкиваются страны с валовым доходом ниже среднего, в том числе и Украина. С учетом особенностей государственных инструментов по инновационной активности предприятий обоснована целесообразность использования различных видов поддержки развития инновационных технологий - со стороны не только государства, но и научно-исследовательских учреждений и самих предприятий. Проведен анализ эффективности налоговых стимулов инновационной активности предприятий введущих странах мира. Рассмотрены современные аналитические инструменты оценки налогового стимулирования предприятий и определена эффективность налоговых стимулов для их инновационной активности в условиях глобальной цифровизации. Обоснованы возможные направления использования государственных инструментов стимулирования инновационных технологий в Украине. Главное требование налогового стимулирования национальных инноваций заключается в осуществлении субъектом хозяйствования систематической деятельности, направленной на достижение научно-технического прогресса в условиях научной или технологической неопределенности. Налоговые стимулы должны быть доступны инновационным предприятиям независимо от их территориального расположения в пределах государства и размера; позволять вычитать из суммы налога на прибыль инновационных предприятий часть квалифицированных расходов; предоставляться на безвозвратной основе в течение законодательно установленного периода времени; разрабатываться с учетом сведения к минимуму возможностей развития коррупции при предоставлении стимулов и злоупотреблений налогоплательщиками при их использовании. Оценка правительством ожидаемых расходов и выгод от налогово-бюджетного стимулирования инновационной деятельности предприятий Украины должна быть аналогична оценке других видов налоговых расходов с учетом институциональных особенностей развития национальной экономики. The use of innovative technologies implies, on the part of an enterprise, the development of scientific and design strategies for updating manufacturing processes of products, and, on the part of the state, effective tools to stimulate the innovative activity of business entities. Tax incentives lead to a shortfall in public revenues or resources that could be used in other forms of government support. To assess the effectiveness of their use, an analysis of the amount of expenses for their provision and incomes that are received from their use was carried out. For this, the place of innovations in enterprises’ economic activities and their impact on the economy in the context of global digitalization is considered.Directions of innovations’ implementation and their significance in the real sector of the economy are defined. In many countries of the world strategic programs for the development of enterprises’ innovative activities are being developed and improved. Their analysis has shown the relevance of the latter in the context of the implementation of the up-to-date digital technologies. Problems, faced by countries with lower than middle gross income (Ukraine are among them), are outlined. On the basis of peculiarities of state instruments, directed on stimulation of the enterprises’ innovative activity, the expediency of using various types of support for the development of innovative technologies is substantiated - not only from the state, but also fromresearch institutions and enterprises themselves. This can be facilitated by the state through the utilization of appropriate regulatory instruments (budgetary, fiscal, etc.).The analysis of tax incentives effectiveness for innovative activity in advanced countries is carried out. Considered are modern analytical tools for assessing tax incentives for enterprises. The efficiency of tax incentives for their innovative activity in the context of global digitalization has been defined. Possible directions of using state instruments to stimulate innovative technologies in Ukraine have been substantiated. The main requirement for tax incentives for national innovations should be the pursuit by a business entity of activities, aimed at achieving scientific and technological progress in conditions of scientific or technological uncertainty. Tax incentives should be available to innovative enterprises, regardless of their geographic location and size within the state. They should allow the deduction of a part of qualified expenses from the amount of corporate income tax of innovative enterprises. They must be provided on a non-refundable basis within a statutory period of time. They should be designed to minimize the potential for corruption in the provision of incentives and abuse by taxpayers in their use. The government's assessment of expected costs and benefits from fiscal stimulation of innovative activities of Ukrainian enterprises should be similar to the assessment of other types of tax expenses, taking into account the institutional features of the national economic development.